The construction of shared Malaysian identity in the upper secondary English literature classroom - Idrus, Faizah (2012)
In Malaysia, ethnic and cultural tension and conflicts have escalated in the past 5 years bringing undesirable impacts on the nation’s economy and, most importantly, on inter-ethnic relationships. In line with the government’s 1Malaysia effort to produce a more integrated society, this study proposes the need to construct a shared Malaysian identity, starting from the classroom, which is facilitated by teachers through the use of Malaysian short stories. This proposition, amidst the differences in cultural, religious and beliefs systems, aims to close the ethnic and cultural divide and cultivate widespread inter and intra cultural awareness. The study is grounded in the notion of hybridity in the Third Space espoused by Bhabha (1994) and ameliorated and geared towards the classroom context by the works of Gutiérrez (1999, 2004, 2008). The inquiry was designed using primarily qualitative research instruments employing non-participant classroom observations, semi-structured interviews with 7 English Language teachers, and group interviews with 6 groups of students from 4 different schools in Kuala Lumpur. A one-day workshop was also conducted with the 7 teachers to introduce new Malaysian short stories and also for the purpose of sharing experiences in teaching literature in English. This data source was then supported by secondary quantitative data derived from self-completion questionnaires administered to the students of the teachers involved in this study. The findings from the analyses of the results show various attitudes, beliefs and teaching and practices in the English language classroom in response to the notion of constructing a shared identity in the Third Space. The notion of the hidden curriculum is also investigated to determine how it can be usefully theorized towards identity construction in the classroom. On the one hand, students mainly accepted the shared identity concept as a basis for classroom practice, whilst teachers had a range of views about this idea. In the conclusion, the thesis explores the implications of the classroom practices adopted by the teachers in this study as part of the process of constructing a shared Malaysian identity. It also examines the plausibility of and barriers to creating an awareness of the Third Space through the use of narratives produced by local writers, both as a medium for developing the skills to access the Third Space and also as the container of messages about Malaysian society and identity. Finally, this study suggests the way forward for realizing the country’s aspiration of a unified society and becoming a full-fledged developed country, which can possibly start in the classrooms.